Angular dependence of the magnetoelectric effect in orthorhombic HoMnO3 films - Ziese, M. (2011)
Epitaxial orthorhombic HoMnO3 films were grown on Nb-doped SrTiO3 (001) single-crystal substrates. X-ray diffractometry showed a uniform crystallographic orientation with the c axis along the substrate normal and an anisotropic compressive stress along the b axis of the Pbnm structure. The magnetization of the films was dominated by the paramagnetism of the Ho3+ ions; the latter showed a strong anisotropy with respect to the in-plane and perpendicular-to-plane magnetic field direction. The rotational anisotropy of the magnetoelectric effect was measured for magnetic field rotation in the (110)o, (110)o, and (001)o planes. Whereas magnetic field rotation in the (110)o and (110)o planes showed a twofold pattern with the smallest magnetoelectric effect observed in magnetic fields along the c axis, in-plane (001)o magnetic field rotations revealed an intricate rotational symmetry. A magnetic-field-induced crossover was observed from a low-field region with fourfold rotation patterns to a high-field region with rotation patterns up to the 12th order.This complex rotational symmetry arises from spin-orbit coupling of the Ho3+ moments that induces a modulation of the magnetoconductance as well as a magnetoelectric effect through the Maxwell-Wagner mechanism